Flexible single-mode delivery of a high-power 2 μm pulsed laser using an antiresonant hollow-core fiber - Lee, Elizabeth (2020)
We demonstrate flexible single-mode transmission of a high average power 2 µm nanosecond pulse using antiresonant hollow-core fibers (AR-HCFs). 39.1 W average power is delivered using a coiled 1.7 m AR-HCF, which is designed for single-mode guidance and good higher-order mode suppression. The effect of bending on the fiber output power and beam profile is also investigated. The Gaussian-like output beam profile is maintained up to a 7.5 cm bending radius. This is the highest average power delivered by a flexible long HCF in this wavelength without the need for an enclosed controlled environment, to the best of our knowledge.